THE DETECTION OF SARS-COV-2 IN NASOPHARYNGEAL SAMPLES USING AN ANTIGENIC TEST - Catalina Lunca; Cristian Cojocaru; Loredana Liliana Hurjui; Florin Dumitru Petrariu; Elena Cojocaru (Romanian Society of Oral Rehabilitation, 2024)
Objectives: SARS-CoV-2 virus detection on nasopharyngeal specimens to infected individuals was a challenge for the COVID-19 pandemic outbreak. The aim of the study was to compare the performance of antigenic detection of SARS-CoV-2 in nasopharyngeal samples using an immunochromatographic method with molecular detection via qRT-PCR. Materials and Methods: 47 nasopharyngeal exudates were collected from suspected COVID-19 cases. The samples were performed both with the qualitative immuno-chromatographic method for S protein detection in the SARS-CoV-2 structure, fluorescent labelled anti-protein S antibodies and by qRT-PCR test for the qualitative detection of the screening gene E and the specific ORF1ab region of the RNA-SARS-CoV-2. Results: There was a good correlation between the positive antigen tests and the positive PCR assays measured through threshold cycle ORF1ab region (Ct orf). A better correlation was obtained between the antigen test results and the positive qRT-PCR tests when including patients with Ct orf below 25. Conclusions: Antigen testing is helpful for symptomatic people, especially during infectious period. A positive test has a high predictive value for infection, while a negative antigen test result via immuno-chromatography must be confirmed by a qRT-PCR test.